Application of piezo quartz microweights for express out-of-laboratory determination of actual resins in diesel fuels - T. A. Kuchmenko (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2022)
The article shows the possibility of using the piezo quartz microweighting method and a portable device model based on highly sensitive piezoweights for express assessment of the concentration of actual resins in diesel fuel. A comparative characteristic of the methods for determining the actual resins in diesel fuel is given: the standard Budarov method is evaporation to a dry residue under a jet of water vapor to a constant mass, the fractional distillation method is heating to the evaporation temperature, cooling the gas fraction and measuring the volume of the non-distillable residue. The device of highly sensitive quartz piezoweights, the main patterns, characteristics during operation are considered. Samples of diesel fuel of the brand L-0,2-62 GOST 305-82 "Diesel fuel" were selected as objects of research. Technical specifications" of different manufacturers and filling dates provided in the fleet of the FVA RVSN im. Peter the Great (Serpukhov city). The results of a study of diesel fuel according to standard methods for determining the content of actual resins, cetane number, density, kinematic viscosity, acidity, water–soluble acids and alkalis, mechanical impurities and water content, fractional composition - distillation temperatures of 50 and 96% of fuel, flash point in a closed crucible, turbidity temperature and solidification temperature, test on a copper plate are presented. The characteristic of the operational properties of each sample is given. The method of piezo-quartz microweighting with a one-way load of the investigated diesel fuel breakdown of the resonator electrode, mass-sensitive (OAV-type), is applied. The correlation between the results obtained by piezo-quartz microweighting and the standard method was studied. The possibility of using the piezo-quartz microweighting method for the development of express out-of-laboratory determination of non-volatile residue in diesel fuel is positively evaluated.